Socio-behavioral determinants of early vs. long-term HIV infection in Kazakhstan: roles of self-testing, alcohol, drug use and sexual networks - Kuzembayev, Marat; Yermukhanova, Lyudmila S.; Sadeghi, Saeed; Aimbetova, Gulshara; Urazayeva, Aisha; Arynova, Gulbanu; Afshar, Alireza (Frontiers in Public Health, 2025)
BackgroundHuman immunodeficiency virus (HIV) remains a major global public health challenge, with eastern Europe and central Asia experiencing a rapid rise in new infections. In Kazakhstan, structural barriers and substance use complicate prevention and care. This study aimed to determine the socio behavioral determinants of recent vs. long term HIV infection and identify predictors of baseline viral load and CD4 count among newly diagnosed adults.MethodsWe conducted a retrospective cross-sectional study of 452 adults diagnosed with HIV in 2023–2024 at the Kostanay Regional Center for Prevention and Control of AIDS. Clinical data were extracted from medical records and behavioral information collected via structured questionnaires. Infection stage was defined as recent (< 6 months) or long term (>6 months). Logistic regression identified factors associated with infection stage; linear regression assessed predictors of log10 viral load and CD4 count.ResultsParticipants were predominantly married (63.3%) and middle aged (mean 41.5 years). Self reported alcohol (80.8%) and drug use (67.5%) were common, and 80.8% had used an HIV self test prior to diagnosis. Early infection declined from 27.4% in 2023 to 16.2% in 2024. Logistic models showed that male gender, any alcohol use and lifetime drug use were associated with higher odds of recent infection, while each additional sexual partner increased the odds of long term infection. Early cases were more likely to have self tested and to report recent sexually transmitted infections. Older age predicted higher viral load and lower CD4 count, whereas recent infection was associated with better immunological status.ConclusionEarly detection is occurring among substance users through self testing and harm reduction programs, yet older adults and those with multiple partners remain at risk for delayed diagnosis. Integrated interventions that couple self testing with substance use services and targeted outreach to older individuals could accelerate progress toward epidemic control.